Human Lysophosphatidylcholine Acyltransferases 1 and 2 Are Located in Lipid Droplets Where They Catalyze the Formation of Phosphatidylcholine - Christine Moessinger; Lars Kuerschner; Johanna Spandl; Andrej Shevchenko; Christoph Thiele (2011)
Phosphatidylcholine (PC) is synthesized by two different pathways, the Lands cycle and the Kennedy pathway. The recently identified key enzymes of the Lands cycle, lysophosphatidylcholine acyltransferase 1 and 2 (LPCAT1 and -2), were reported to localize to the endoplasmic reticulum and to function in lung surfactant production and in inflammation response. Here, we show in various mammalian cell lines that both enzymes additionally localize to lipid droplets (LDs), which consist of a core of neutral lipids surrounded by a monolayer of phospholipid, mainly PC. This dual localization is enabled by the monotopic topology of these enzymes demonstrated in this study. Furthermore, we show that LDs have the ability to locally synthesize PC and that this activity correlates with the LPCAT1 and -2 expression level. This suggests that LPCAT1 and -2 have, in addition to their known function in specialized cells, a ubiquitous role in LD-associated lipid metabolism.